Legal Protection For Creditors To Ensure The Fulfillment Of State-Owned Enterprises (Persero)’S Liabilities In The Indonesian Legal System - Heru Pramono (Prophetic Law Review, 2023)
The professional management of State-Owned Enterprise Ltd. (Persero) will increase profits from business operations, which will in-turn increase state income. On the other hand, the less professional management of State-Owned Enterprises will lead to a negative impact due to economic losses. To prevent disputes between debtors and creditors when the Limited Liability State-Owned Enterprises (Persero) 1 suffers losses, the state has regulated a resolution through a bankruptcy mechanism to protect the rights of creditors. However, as a matter of fact, there are numerous inconsistent judicial interpretations regarding state capital participation in the State-Owned Enterprise Persero. In addition, disharmony of legal regulations has resulted in different views and understanding of judges regarding the legal position of State-Owned Enterprises in the implementation of bankruptcy and state finances. Based on these inconsistencies and disharmony, this study addresses three essential research questions: first, why is it necessary to apply legal protection to ensure that State-Owned Enterprises (Persero) fulfil its liabilities? Second, what will be the future legal protection for creditors to ensure that State-Owned Enterprises as debtors fulfil their liabilities? This normative legal research used statutory, conceptual, and case study approaches. This research concludes that legal certainty is needed to ensure creditor protection in the bankruptcy mechanism for State-Owned Enterprises. This legal certainty will only be achieved by changing the existing regulations through confirming the legal norm that the capital invested in the State-Owned Enterprise is the financial right of the State-Owned Enterprise Persero and is no longer included in state finances managed under the State Budget. This legal norm is necessary to avoid legal disharmony and inconsistency due to the diverse definitions of capital participation in State-Owned Enterprises (Persero) in bankruptcy decisions. This research initiates reformulation and clarity regarding the meaning of State capital participation in State-Owned Enterprises Persero.Keywords: State-Owned Enterprises, Creditors, Bankruptcy Perlindungan Hukum Bagi Kreditur Untuk Menjamin Pemenuhan Kewajiban Badan Usaha Milik Negara (Persero) Dalam Sistem Hukum Indonesia AbstrakPengelolaan PT Badan Usaha Milik Negara (Persero) yang profesional akan meningkatkan keuntungan operasional usaha yang pada gilirannya akan meningkatkan pendapatan negara. Di sisi lain, pengelolaan Badan Usaha Milik Negara yang kurang profesional akan menimbulkan dampak negatif berupa kerugian ekonomi. Untuk mencegah terjadinya perselisihan antara debitur dan kreditur apabila Badan Usaha Milik Negara (Persero) 1 mengalami kerugian, negara telah mengatur penyelesaian melalui mekanisme kepailitan untuk melindungi hak-hak kreditur. Namun pada kenyataannya, terdapat banyak penafsiran hukum yang tidak konsisten mengenai penyertaan modal negara pada Badan Usaha Milik Negara Persero. Selain itu, ketidakharmonisan peraturan perundang-undangan mengakibatkan adanya perbedaan pandangan dan pemahaman hakim mengenai kedudukan hukum Badan Usaha Milik Negara dalam pelaksanaan kepailitan dan keuangan negara. Berdasarkan inkonsistensi dan disharmoni tersebut, penelitian ini menjawab tiga pertanyaan penting penelitian: pertama, mengapa perlu diterapkan perlindungan hukum untuk menjamin Badan Usaha Milik Negara (Persero) memenuhi kewajibannya? Kedua, bagaimana perlindungan hukum ke depan bagi kreditur untuk memastikan BUMN sebagai debitur memenuhi kewajibannya? Penelitian hukum normatif ini menggunakan pendekatan perundang-undangan, konseptual, dan studi kasus. Penelitian ini menyimpulkan bahwa kepastian hukum diperlukan untuk menjamin perlindungan kreditur dalam mekanisme kepailitan Badan Usaha Milik Negara. Kepastian hukum tersebut hanya dapat dicapai dengan mengubah peraturan yang ada melalui penegasan norma hukum bahwa modal yang ditanamkan pada Badan Usaha Milik Negara merupakan hak keuangan Badan Usaha Milik Negara Persero dan tidak lagi termasuk dalam keuangan negara yang dikelola di bawah naungan Negara. Anggaran. Norma hukum ini diperlukan untuk menghindari disharmoni dan inkonsistensi hukum akibat beragamnya definisi penyertaan modal pada Badan Usaha Milik Negara (Persero) dalam putusan pailit. Penelitian ini mengawali reformulasi dan kejelasan mengenai makna penyertaan modal negara pada Badan Usaha Milik Negara Persero.Kata Kunci: Badan Usaha Milik Negara, Kreditur, Kepailitan